Antidesma montis-silam - Tsen, S.; Hor, C.S.; Damit, A.; Khoo, E.; Maryani, A.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Antidesma montis-silam is a tree, endemic to Sabah. It is found on the lowland ultramafic forest of eastern Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are 40 km2 and 3,680.3 km2, respectively. Individuals outside of protected area can be at risk of habitat loss but this species is well represented within protected area. Hence, it is assessed as Near Threatened. Antidesma montis-silam is endemic to Sabah, Malaysia. It is recorded from ultramafic substrate in eastern Sabah. This species is known from fewer than ten collection localities, but the majority of these are inside protected areas and not exposed to threats. Therefore, number of locations is not calculated for this species.